Persistent prevention of oxaliplatin-induced peripheral neuropathy using calmangafodipir (PledOx®): a placebo-controlled randomised phase II study (PLIANT). (4th March 2018) - Glimelius, Bengt; Manojlovic, Nebojsa; Pfeiffer, Per; Mosidze, Baadur; Kurteva, Galina; Karlberg, Mia; Mahalingam, Devalingam; Buhl Jensen, Peter; Kowalski, Jan; Bengtson, Marie; Nittve, Malin; Näsström, Jacques
Abstract: Purpose: Oxaliplatin causes disabling acute and chronic peripheral neuropathy. We explored the preventive effects of calmangafodipir, mimicking the mitochondrial enzyme manganese superoxide dismutase, thereby protecting cells from oxidative stress, in a placebo-controlled, double-blinded randomised phase II study (ClinicalTrials.gov.NCT01619423) in patients with metastatic colorectal cancer (mCRC). Patient and methods: mCRC patients treated with modified FOLFOX-6 (folinic acid 200 mg/m 2, 5-fluorouracil bolus 400 mg/m 2, oxaliplatin 85 mg/m 2 and 5-fluorouracil 2400 mg/m 2 continuous infusion for 46 h) every fortnight for 8 cycles in first or second line were eligible. Calmangafodipir was given in a phase I dose-finding and in a phase II placebo-controlled study, as a 5-min infusion 10 min prior to oxaliplatin. Neurotoxicity was evaluated by the physician using the Oxaliplatin Sanofi Specific Scale and by the patient using the cold allodynia test and the Leonard scale. Results: Eleven patients were included in phase I without any detectable toxicity to calmangafodipir. In the phase II study, 173 patients were randomised to placebo ( n  = 60), calmangafodipir 2 µmol/kg ( n  = 57) and calmangafodipir 5 µmol/kg ( n  = 45, initially 10 µmol/kg, n  = 11). Calmangafodipir-treated patients (all three doses pooled) had less physician graded neurotoxicity (odds ratio (90% confidence interval one-sided upper level) 0.62(1.15), p  = .16), significantly less problems with cold allodynia (mean 1.6 versus 2.3, p  < .05) and significantly fewer sensory symptoms in the Leonard scale (cycle 1–8 mean 1.9 versus 3.0, p  < .05 and during follow-up after 3 and 6 months, mean 3.5 versus 7.3, p  < .01). Response rate, progression-free and overall survival did not differ among groups. Conclusions: Calmangafodipir at a dose of 5 µmol/kg appears to prevent the development of oxaliplatin-induced acute and delayed CIPN without apparent influence on tumour outcomes.